KOMODIFIKASI TOKOH AGAMA DALAM TAYANGAN IKLAN TELEVISI: STUDI KASUS USTADZ MAULANA DALAM IKLAN OPERATOR SELULER TELKOMSEL VERSI HAJI - Zafirah Quroatun ’Uyun (Al'Adalah, 2015)
The phenomenon of commodification of religious leaders one example of how the television industry to enter the realm that had so "sacred" Muslim community. Observing ad telkomsel Hajj version glanceit appears that this broadcast the Islamic religion that brought the religious awareness by displaying the figure cleric who had been constructed as a role model in religious Islamic society. However, when examined critically visualize display advertising led to the use of religious leaders in support of the promotion of products belonging to cellular card provider. It means that the presence of religious leaders into supporting commodity from a material commodity, even commodified for the sake of financial gain. In a wider context this addis playing the profane religious values which is considered sacred and is compromised by the logic of the market. Without realizing the presence of religious leaders in the ad become an instrument ofthe legality of the material product.